Clay-Based Materials for Heavy Metals Adsorption: Mechanisms, Advancements, and Future Prospects in Environmental Remediation - Pengsheng Wang; Xinkai Shen; Shusheng Qiu; Long Zhang; Yanping Ma; Jinbao Liang (Crystals)
Given the severe threats posed by heavy metal pollution to ecological environments and human health, developing effective remediation technologies is of paramount importance. This review delves into the mechanisms, recent advancements, and future prospects of clay mineral-based materials in the adsorption of heavy metals. Clay minerals such as kaolinite, montmorillonite, and bentonite have demonstrated immense potential for the removal of heavy metals from water and soil due to their natural abundance, low cost, and high efficiency. This article summarizes the latest advancements in the adsorption of heavy metals like chromium, copper, lead, cadmium, arsenic and hydrargyrum by clay minerals, while examining how chemical and physical modifications can enhance the adsorption capacity, selectivity, and stability of these minerals. Furthermore, this review discusses how factors such as pH, temperature, and ionic strength affect adsorption efficiency and outlines challenges and future research directions for optimizing clay-based adsorbents in environmental applications.